Cambodia : Fifth Review Under the Poverty Reduction and Growth Facility and Request for Waiver of a Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2002)
This paper assesses Cambodia's Fifth Review Under the Poverty Reduction and Growth Facility (PRGF) and a Request for Waiver of a Performance Criterion. Cambodia's medium-term reform program supported by the PRGF is aimed at sustaining economic growth with low inflation, reducing poverty, and accelerating development. Performance during the first two years of the PRGF-supported program has generally been positive. Macroeconomic stability has been maintained with economic growth averaging 7 percent and low inflation. The macroeconomic program for 2002 concentrates on a continued reorientation of fiscal policy.